Protective effect of aqueous extracts from Rhizopus oryzae on liver injury induced by carbon tetrachloride in rats. (11th December 2014) - Suzuki, Takehito; Fukuoka, Hideo; Ushikoshi, Setsuo; Sato, Reiichiro; Morita, Hidetoshi; Takizawa, Tatsuya
Abstract Hepatoprotective effects of Rhizopus oryzae/ U‐1 aqueous extract (RU) were demonstrated in carbon tetrachloride (CCl4)‐induced liver‐injured rats. In order to investigate the RU effects, the rats were administered RU at a dose of 10 or 100 mg/kg of body weight for 10 days before induction of the liver injury by oral administration of CCl4 (125 mg/kg body weight). (i) Pretreatment with RU caused a significant decrease in serum lactate dehydrogenase (LDH), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities that were increased by the administration of CCl4. (ii) RU pretreatment (100 mg/kg) increased 5‐bromo‐2′‐deoxyuridine incorporation at 48 h after CCl4 treatment in hepatocytes. (iii) Histological hematoxylin and eosin staining of the liver showed that RU pretreatment reduced the damage induced by CCl4 administration. (iv) Reverse transcriptase PCR analysis showed RU retreatment caused a transient but significant increase in hepatocyte growth factor (HGF) and a sustained and significant increase in insulin‐like growth factor‐I (IGF‐I) gene expression in hepatocytes injured by CCl4 treatment. From these results, we conclude that oral pre‐administration of RU was effective to suppress liver injury induced by the subsequent oral CCl4 administration, and RU‐induced increase in IGF‐I and HGF gene expression may be, even in part, involved in biological actions of RU in rats.